Получение гидроксида никеля методом низкотемпературного гомогенного осаждения - Коваленко, Вадим Леонидович; Коток, Валерий Анатольевич; Баскевич, Александр Сергеевич (НТУ "ХПИ", 2017)
Гидроксид никеля является активным веществом суперконденсаторов, которые широко используются в качестве источника питания различных электрических и электронных устройств. Для использования в суперконденсаторах необходим гидроксид никеля с высокими электрохимическими характеристиками, при этом технология синтеза должна быть энергосберегающей. Одним из наиболее перспективных методов синтеза гидроксида никеля является гомогенное осаждение, проводимое путем гидротермальной обработки при 90-95 °С раствора нитрата никеля и мочевины. Недостатком метода является высокая энергозатратность. В работе предложен метод низкотемпературного гомогенного осаждения гидроксида никеля. Методом РФА показано, что полученный гидроксид представляет из себя альфа-форму невысокой кристалличности. Изучены электрохимические характеристики образца никель гидроксида, полученного предложенным методом. Показаны высокие удельные ёмкости 110-190 Ф/г 70-115 мА*ч/г.

Nickel hydroxide is used as an active substance of supercapacitors, which are widely used as power sources for various electric devices and electronics, especially for starting and working of the difference electric engines and in the uninterrupted power supply devices. According to high speed of the charge-discharge process, for using in the supercapacitors nickel hydroxide must has high electrochemical activities, and synthesis technology must be energy saving. One of the perspective method of the nickel hydroxide synthesis is homogeneous precipitation, carried out by hydrothermal treatment of solution of nickel nitrate and carbamide under 90-95 °С. The disadvantage of this method is high energy consumption. The new method of low temperature homogeneous precipitation of the nickel hydroxide under room temperature has been proposed. Precipitation duration of proposed method was 6 month. Nickel hydroxide obtained by proposed low temperature homogeneous precipitation has been characterized. By XRD method it was shown that nickel hydroxide is α-Ni(OH)2 with low crystallinity. Electrochemical characteristics of nickel hydroxide, obtained by proposed method, have been investigated. Cycling voltammogramm show that nickel hydroxide, obtained by proposed method, have high electrochemical activity and high reversibility. By galvanostatic charge-discharge cycling in the siupercapacitor mode it was shown high electrochemical capacities 110-190 F/g and 70-115 mА*h/g. Also it was indicated that increasing of discharge current density give the increasing of specific capacity of nickel hydroxide as a result of the particles destruction.
The obtaining of nickel hydroxide by low temperature homogeous precepitation method
Keywords: суперконденсатор; емкость удельная; энергозатратность; nickel hydroxide; supercapacitor; specific capacities